EVALUATION OF MECHANICAL BEHAVIOR OF Al MMC USED IN STIR CASTING METHOD - M. , SIVANESAN; S. , SURESH KUMAR (International Journal of Psychosocial Rehabilitation, 2020)
This paper is about the aluminum MMCs, which are preferred to other conventional materials in fields such as aeronautics, automotive or automobiles, and marine applications owing to their improved properties like good wear resistance and high strength-to-weight ratio. In this work, we tried to synthesize MMC using an aluminum material called 6061Al as matrix material, which is later reinforced with ceramic Al2O3 particulates using the liquid metallurgy route using the stir casting method.